A new species of Microlicia (Melastomataceae) from Bolivia and Brazil, a new synonym, and an identification key for the genus in Mato Grosso, Brazil - Versiane, Ana Flávia Alves; Da Silva, Diego Nunes; Romero, Rosana (Phytotaxa, 2020)
Microlicia windischii is a new species described from Noel Kempff Mercado National Park, Santa Cruz de la Sierra, Bolivia, and Serra Ricardo Franco State Park, Mato Grosso, Brazil. We provide a detailed description of the new species and comparisons with its morphological relatives M. acuminata, M. arenariifolia, M. consimilis, M. juniperina, and M. multicaulis. Microlicia windischii is characterized by the linear-oblong leaf blades and subisomorphic stamens with concolorous and polysporangiate anthers. We also include an identification key for the four species of Microlicia from Mato Grosso and propose to synonymize M. souzae-limae under M. helvola.